Sunk cost effect in the decision-making process: an analysis with accounting and business administration students - Jéssica Priscila Rodrigues Meireles; Yuri Gomes Paiva Azevedo; Lucas Allan Diniz Schwarz; Hellen Bomfim Gomes (Revista Ambiente Contábil, 2019)
Purpose: The objective of this paper was to analyze the influence of the sunk cost effect in the decision-making process of Accounting and Business Administration undergraduate students of the Federal University of Rio Grande do Norte.